Inhibition of HMGB1 Suppresses Hepatocellular Carcinoma Progression via HIPK2-Mediated Autophagic Degradation of ZEB1 - Zhu, Wei; Li, Jun; Zhang, Yuheng; Zhu, Zhengyi; Liu, Hanyi; Lin, Yunzhen; Hu, Anyin; Zhou, Jingchao; Ren, Haozhen; Shi, Xiaolei (Frontiers in Oncology, 2021)
Autophagy is a conserved catabolic process maintaining cellular homeostasis and reportedly plays a critical role in tumor progression. Accumulating data show that autophagic activity is inhibited in HCC. However, the underlying molecular basis of impaired autophagy in HCC remains unclear. In this study, we revealed that autophagic activity was mediated by HMGB1 in a HIPK2-dependent way. Targeting HMGB1 could repress the degradation of HIPK2, which promoted the autophagic degradation of ZEB1 via reprogramming glucose metabolism and stimulating AMPK/mTOR signaling pathway. Moreover, we demonstrated that HMGB1 deficiency induced selectively degradation of ZEB1 by autophagy was responsible for HCC growth inhibition. Lastly, we found the combination of HMGB1 inhibitor and rapamycin, an autophagy inducer, achieved a better therapeutic effect of HCC. These results demonstrate that autophagy is controlled by HMGB1 and targeting HMGB1 could suppress HCC progression via HIPK2-mediated autophagic degradation of ZEB1.